An edible erodible semi‐interpenetrating polymer network as a microcapsule shell to protect probiotic bacteria during reconstitution of powdered infant formula at elevated temperatures. Issue 21 (2nd February 2022) - Penhasi, Adel; Baluashvili, Israel; Shalev, Deborah E.
Abstract: Probiotic bacteria (PB) are added to some powdered infant formula (PIF) to fortify their composition and to make them more similar to human breast milk. However, the effectiveness of the probiotics may disappear when PIF is reconstituted at 70°C according to the WHO guidelines designated to destroy possible contaminants. We present a unique microencapsulation technique to effectively protect Bifidobacterium breve M‐16 V ( B. breve ) during the reconstitution process at 70°C, to enable their incorporation into PIF. The microcapsules were prepared by a wet granulation process to encompass the bacteria within a core matrix which was subsequently coated by two consecutive protective layers including an edible erodible semi‐interpenetrating polymer network (IPN) as the outer layer. The semi‐IPN sample films and the final microcapsules were characterized using different analytical methods. The survival of the microencapsulated bacteria during reconstitution in hot water (70°C) was evaluated and compared to that of the free bacteria. While the viability of the free bacteria was significantly reduced during the reconstitution process, the microencapsulated bacteria maintained high viability. The degree of PB protection was strongly influenced by the structure of the microcapsules, the composition and thickness of the semi‐IPN layer, and the content of the bacteria. Abstract :